Secondary school students’ school-related stressors during the coronavirus disease (COVID-19) pandemic in Sabah, Malaysia - Wider, Walton; Chua, Bee Seok; Mutang, Jasmine Adela; Pan, Lee Ching (Frontiers in Education, 2023)
Due to the rapid spread of the COVID-19 pandemic and the disruption of education systems worldwide, secondary schools in Malaysia have shifted to online classes to ensure educational continuity. Therefore, it was necessary to investigate the various effects of the COVID-19 pandemic on secondary school students. A self-reported survey with closed and open-ended questions was used to collect data involving 1067 secondary school students from eight schools in Sabah, Malaysia. The participants were mostly male (53.4%), with a mean age of 14.8 (SD = 1.64). The study involved students from various levels/grades, including transition class, forms 1-5, lower six, and upper six. Students faced a variety of school-related stressors, including academic failure due to a poor online course; general mental health issues; a poor internet connection; a lack of in-person interaction; a SOP restriction; an inability to focus; too many homework assignments; burnout; becoming lazier; home conditions; and financial difficulties. The implications for classroom practice, policy formulation, and future research are examined.